The Aplications of Rule Fiqh "The Fatwa Changes Because the Change of Period and Place" at fatwa of The Indonesian Council of Ulama From Years 1975 Until Years 2011 - Yahya, Yahya, Dr.Muindinillah Basri, M.A (2013)
Purpose of this thesis is to learn rule fiqh "The fatwa changes because the change of period and place" and to gain the application in fatwa issued by The Indonesian Council of Ulama from years 1975 until years 2011. This thesis used analytic descriptive method and literateur research type. The principal problem in this research is 2: First, what is the meaning of rule "the fatwa changes because the change of period and place". Second, what is application rule "the fatwa changes because the change of period and place in fatwa issued by The Indonesian Council of Ulama from years 1975 until years 2011? The result from this research is the meaning of rule "the fatwa changes because the change of period and place" is the fatwa from mufti can be change because a reason of the reasons change of fatwa in the specific reality. And the applications of this rule in fatwa issued by The Indonesian Council of Ulama from years 1975 until years 2011 have 2 fatwas: First fatwa, forbidden to meningitis vaccine that used material from a pig and/or in procces manufacturing happened transmission between material pig for obligatory hajj and obligatory umrah. Which is the previous fatwa says, we permitted use when we are in urgent condition. Second fatwa, about Qibla. Qibla of Indonesia is the northwest with diserve position, appropriate the layout of each, which is the first fatwa that the Qibla of Indonesia is only to the west.